The prediction, quantification and evaluation of advanced process control benefits - Bawden, Neil Martin (My University, 2016)
It has been suggested that the inability to quantify the financial benefits of advanced process control is a. key barrier to hs more widespread use and acceptance. This report discusses the financial analysis of advanced process control opportunities. Potential benefits of advanced control are predicted by considering the power spectral density of load disturbances likely to affect the control system, and the ideal characteristlcs of feedback systems as proposed by H.W. Bode. Financial ratio analysis and modem measures of profitabilty, such as Discounted Cash Flow Rate of Return (DCFRR) and Net Present Value (NPV) are used to evaluate the economic potential of control opportunities fer an organisation. The results indicate that financial benefits of advanced process control strategies can be predicted, quantified and then evaluated, with the ultimate aim of improving the overall financial position of all organisation.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg in partial fulfillment of the requirements for the degree of Master of Science in Engineering. Johannesburg 1992
Keywords: Chemical process control.